Risk Perceptions of SARS-CoV-2 in the UK: A City-wise Analysis - Raza, Naba (2022)
Covid-19, which was first announced as a pandemic in early 2020, has recently mutated into a new fast-spreading version. From past lockdowns and coronavirus statistics, it is evident that preventive measures can help reduce the number of daily positive cases. Often, the adoption of behaviors to avoid a threat is influenced by how people perceive it. Thus, in this paper, I present results from a nationally balanced cross-sectional survey (N = 300) on how people perceive the risk of covid-19 infection and how those perceptions associate with preventive behaviors in ten cities across the UK.